2010
DOI: 10.1017/s0950268810002256
|View full text |Cite
|
Sign up to set email alerts
|

Is hand, foot and mouth disease associated with meteorological parameters?

Abstract: We examined the relationship between meteorological parameters and hand, foot and mouth disease (HFMD) activity. Meteorological data collected from 2000 to 2004 were tested for correlation with HFMD consultation rates calculated through the sentinel surveillance system in Hong Kong. The regression model constructed was used to predict HFMD consultation rates for 2005-2009. After adjusting for the effect of collinearity, mean temperature, diurnal difference in temperature, relative humidity, and wind speed were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
139
5
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(176 citation statements)
references
References 29 publications
28
139
5
1
Order By: Relevance
“…These results were consistent with previous studies conducted outside mainland China (Ma et al 2010;Onozuka and Hashizume 2011). However, another study on the short-term effects of daily meteorological factors on the HFMD showed relative humidity had a negative effect at lag 1 day and positive effects on lag 5-7 days (Wu et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…These results were consistent with previous studies conducted outside mainland China (Ma et al 2010;Onozuka and Hashizume 2011). However, another study on the short-term effects of daily meteorological factors on the HFMD showed relative humidity had a negative effect at lag 1 day and positive effects on lag 5-7 days (Wu et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Multiple linear regression analysis identified temperature as a significant risk factor, which was consistent with the findings of several ecological studies (9,10,12,16) and epidemic trends in Beijing (6)(7)(8). Meanwhile, the univariate analysis showed that temperature was not a significant risk factor.…”
Section: Discussionsupporting
confidence: 87%
“…Data collection: We retrospectively surveyed 8 previously suspected indoor environmental factors for each group (9,10,12,13,16), including (i) indoor temperature and (ii) humidity, which were measured using HM34 humidity & temperature meter; (iii) average classroom area per student, measured using a tape measure; (iv) effective ventilation area, for which the areas of all operable doors and windows were measured using a tape measure (if the doors or windows were inoperable, the corresponding area was excluded); (v) inhaled particulate matter (PM10), which was measured using the LD-5C microcomputer Laser Dust Monitor device; (vi) the ratio of window to floor area (Ac/Ad), where the total area of all windows and the floor was measured using a tape measure and the inoperable areas were subtracted; (vii) indoor solar radiation using the Model ST-85 Autoranging illuminometer device; and (viii) indoor ultraviolet (UV) radiation using the UV-B-254 UV illuminometer device.…”
Section: Methodsmentioning
confidence: 99%
“…A seasonal peak of HFMD occurs in Mayor June of each year, and two peaks were observed in 2011-2013, which is similar to the results of other reports [12,19,22]. Previous studies have demonstrated that seasonal patterns of HFMD were associated with climatic factors, such as temperature, relative humidity, and precipitation [23][24][25][26].…”
Section: Discussionsupporting
confidence: 85%